The Endothelium as a Driver of Liver Fibrosis and Regeneration - Erica Lafoz; Maria Ruart; Aina Anton; Anna Oncins; Virginia Hernández-Gea (Cells, 2020)
Liver fibrosis is a common feature of sustained liver injury and represents a major public health problem worldwide. Fibrosis is an active research field and discoveries in the last years have contributed to the development of new antifibrotic drugs, although none of them have been approved yet. Liver sinusoidal endothelial cells (LSEC) are highly specialized endothelial cells localized at the interface between the blood and other liver cell types. They lack a basement membrane and display open channels (fenestrae), making them exceptionally permeable. LSEC are the first cells affected by any kind of liver injury orchestrating the liver response to damage. LSEC govern the regenerative process initiation, but aberrant LSEC activation in chronic liver injury induces fibrosis. LSEC are also main players in fibrosis resolution. They maintain liver homeostasis and keep hepatic stellate cell and Kupffer cell quiescence. After sustained hepatic injury, they lose their phenotype and protective properties, promoting angiogenesis and vasoconstriction and contributing to inflammation and fibrosis. Therefore, improving LSEC phenotype is a promising strategy to prevent liver injury progression and complications. This review focuses on changes occurring in LSEC after liver injury and their consequences on fibrosis progression, liver regeneration, and resolution. Finally, a synopsis of the available strategies for LSEC-specific targeting is provided.